2009
DOI: 10.1542/peds.2008-1126
|View full text |Cite
|
Sign up to set email alerts
|

Twin Gestation and Neurodevelopmental Outcome in Extremely Low Birth Weight Infants

Abstract: Objective To compare the risk-adjusted incidence of death or neuro-developmental impairment at 18–22 months corrected age, between twin and singleton extremely low birth weight infants. Hypothesis Twin gestation is independently associated with increased risk of death or adverse neuro-developmental outcomes at 18–22 months corrected age in extremely low birth weight infants. Design/Methods Retrospective study of inborn extremely low birth weight infants (BW 401– 1000g) admitted to NICHD Neonatal Research N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 24 publications
4
48
2
3
Order By: Relevance
“…The majority of the SGA infants were of male gender, and from other studies it is known that female neonates have a better chance of survival compared to their male peers [28][29][30] . Interestingly male gender did not affect the survival of our SGA infants in a negative way.…”
Section: Sga and Aga Infantsmentioning
confidence: 88%
See 1 more Smart Citation
“…The majority of the SGA infants were of male gender, and from other studies it is known that female neonates have a better chance of survival compared to their male peers [28][29][30] . Interestingly male gender did not affect the survival of our SGA infants in a negative way.…”
Section: Sga and Aga Infantsmentioning
confidence: 88%
“…Several studies have shown that a multiple pregnancy is a high risk situation resulting in a significantly higher prevalence of morbidity and poor survival [26,28] . 22.8% of our infants were part of a multiple pregnancy, which may have influenced outcome.…”
Section: Survival and Neonatal Morbiditymentioning
confidence: 99%
“…Cognitive development is impaired in twins compared to singletons according to the Baley Scales of Infant Development Index [82,83] in preterm infants. There is consistent cognitive disadvantage among twins seen in population-based studies [84] .…”
Section: Morbiditymentioning
confidence: 99%
“…We have previously shown that ELBW twins have a higher risk of death or neurodevelopmental handicap compared with singletons in the same birth-weight category. 6 The objective of the current study was to evaluate the comparative risk of death or neurodevelopmental handicap in higher-order multiples (triplets or higher order) compared with twins and singletons. The primary outcome of interest was death or neurodevelopmental impairment (NDI) at 18 to 22 months of age.…”
mentioning
confidence: 99%